Technoeconomics, concepts and cases - Wright, J. C. (Asian Productivity Organization, 1983)
This book introduce about a cost approach to engieering materials production. Cost centress and cost streams. Cost of capital and depreciation. Discounted cash flow techniques. Case study of a DCF project appraisal..., sense of time and scale. Case study of an industry sectorstell founding...